2001
DOI: 10.1124/mol.59.3.420
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Pharmacological Characterization of a Fourth Histamine Receptor (H4) Expressed in Bone Marrow

Abstract: Histamine is a multifunctional hormone that regulates smooth muscle contraction in the airways, acid secretion in the gut, and neurotransmitter release in the central nervous system through three well characterized receptor subtypes, H(1), H(2), H(3), respectively. As part of a directed effort to discover novel G-protein-coupled receptors through homology searching of genomic databases, we identified a partial clone (GPCR105) that had significant homology to the recently identified histamine H(3) receptor cDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
428
2
16

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(469 citation statements)
references
References 22 publications
23
428
2
16
Order By: Relevance
“…49 Additionally, the recent discovery of the h4 receptor primarily expressed in bone marrow and eosinophils, but undetected in brain tempts speculation of a peripheral immune target particularly with respect to asthma and allergy, to which clozapine has moderate affinity. 50 The current data confirm and extend on previous pharmacological 26,27 and mRNA expression studies that suggested the existence of multiple muscarinic receptors on blood lymphocytes. 33,63,51,52 While mRNA for m3, m4, and m5 receptors has been reported in mononuclear cells, the additional detection of m3 and m4 mRNA in neutrophils and stromal cells remains a novel finding.…”
Section: Discussionsupporting
confidence: 90%
“…49 Additionally, the recent discovery of the h4 receptor primarily expressed in bone marrow and eosinophils, but undetected in brain tempts speculation of a peripheral immune target particularly with respect to asthma and allergy, to which clozapine has moderate affinity. 50 The current data confirm and extend on previous pharmacological 26,27 and mRNA expression studies that suggested the existence of multiple muscarinic receptors on blood lymphocytes. 33,63,51,52 While mRNA for m3, m4, and m5 receptors has been reported in mononuclear cells, the additional detection of m3 and m4 mRNA in neutrophils and stromal cells remains a novel finding.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, by altering the lipid environment, apoE deficiency may reduce the total number of H 3 receptor binding sites available for ligand binding in the amygdala, hippocampus, and cortex. Recently, the H 4 receptor was cloned and characterized (Nakamura et al, 2000;Oda et al, 2000;Liu et al, 2001;Morse et al, 2001;Nguyen et al, 2001;Zhu et al, 2001). To determine whether H 4 signaling was involved in the observed effects on object recognition, we tested mice treated with the H 4 receptor agonist and H 3 receptor antagonist clobenpropit (Oda et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type and Apoe -/-mice (3-5 months old) received saline, thioperamide, or clobenpropit during the training (day 4) and retention (day 5) sessions. The recently cloned H 4 receptor (Oda et al, 2000;Liu et al, 2001;Morse et al, 2001;Nguyen et al, 2001;Zhu et al, 2001) was found to have an affinity for H 3 -specific ligands. To rule out the possible contribution of the H 4 receptor to the effects of thioperamide, we also treated wild-type and Apoe -/-mice with clobenpropit, None of the differences between wild-type and Apoe -/-mice were significant.…”
Section: Effects Of H 3 Ligands On Novel Object Recognition In Wild-tmentioning
confidence: 99%
“…Histamine was originally considered a mediator of acute inflammatory and immediate hypersensitivity reactions but is now believed to also affect chronic inflammatory processes and to regulate the immune response. [10,11] The effects of histamine are mediated through at least four distinct cell surface, G-protein-coupled receptors (histamine H 1 , H 2 , H 3 and the newly identified H 4 ) [12][13][14][15][16][17] and eosinophils have been suggested to express all of these subtypes [10,11]. A fifth histamine receptor, located intracellularly and denoted histamine H IC , has also been described in haematopoietic cells.…”
Section: Introductionmentioning
confidence: 99%